The role of combined ion-beam radiotherapy (CIBRT) with protons and carbon ions in a multimodal treatment strategy of inoperable osteosarcoma - Seidensaal, Katharina; Mattke, Matthias; Haufe, Sabine; Rathke, Hendrik; Haberkorn, Uwe; Bougatf, Nina; Kudak, Andreas; Blattmann, Claudia; Oertel, Susanne; Kirchner, Marietta; Büsch, Christopher; Kieser, Meinhard; et al. (Radiotherapy and oncology, 2021)
Background - To investigate the role of combined ion-beam radiotherapy (CIBRT) with protons and carbon ions in a multimodal treatment strategy of inoperable osteosarcoma; final analysis of a one-armed, single center phase I/II trial. - Methods - Between August 2011 until September 2018, 20 patients with primary (N = 18), metastatic (N = 3), or recurrent (N = 2) inoperable pelvic (70%) or craniofacial (30%) osteosarcoma were treated with protons up to 54 Gy (RBE) and a carbon ion boost of 18 Gy (RBE) and followed until May 2019. A Fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) was performed before CIBRT in search for a prognostic factor. The primary endpoint was toxicity. Secondary endpoints included treatment response, global, local and distant progression free survival (PFS, LPFS and DPFS) and overall (OS), among others. - Results - The median age was 20; all patients finished treatment per protocol. LPFS, DPFS, PFS and OS were 73%, 74%, 60% and 75% after one year and 55%, 65% 65.3%, 45% and 68% after two years, respectively. The median clinical target volume (CTV) was 1042 cc and 415 cc for the primary and boost plan, respectively. Craniofacial localization, lower uptake of FDG in PET/CT and boost plan CTV ≤ median were associated with improved overall survival (p = 0.039, p = 0.016 and p = 0.0043, respectively). No acute toxicities > grade III were observed. We observed one case of secondary acute myeloid leukemia (AML) seven months after CIBRT for recurrent disease and one case of hearing loss. - Conclusion - CIBRT shows a favorable toxicity profile and promising results particularly for patients with inoperable craniofacial osteosarcoma.